Thermochemical production of sodium borohydride from sodium metaborate in a scaled-up reactor - Eom, KwangSup; Cho, EunAe; Kim, MinJoong; Oh, SeKwon; Nam, Suk-Woo; Kwon, HyukSang (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
Sodium borohydride (NaBH4) is a safe and practical hydrogen storage material for on-board hydrogen production. However, a significant obstacle in its practical use on-board hydrogen production system is its high cost. Hence, the reproduction of NaBH4 from byproducts that precipitate after hydrolysis is an important strategy to make its use more cost effective. In this work, we focused on the optimization of thermochemical NaBH4 reproduction reaction in a large-scaled reactor (similar to 100 ml), and we investigated the effects of the reaction temperature (400-600 degrees C) and H-2 pressure (30-60 bar) on the NaBH4 conversion yield using Mg as a reducing agent. The conversion yield of NaBO2 to NaBH4 increased with an increase in H-2 pressure to 55 bar and then decreased slightly at GO bar. The yield increased with an increase in the reactor temperature from 400 to 600 degrees C. The maximum yield was 69% at 55 bar and 600 degrees C using homogenized reactants by ball-milling for 1 h under an Ar atmosphere. Though Ca as a reducing agent makes the thermochemical reproduction reaction more favorable, the NaBH4 yield was low after 1 h of production at 55 bar and 600 degrees C. This result may be due to the fact that Ca is not as effective as Mg in catalyzing the conversion of hydrogen gas to protide (H-), which can substitute oxygen actively in NaBO2. Copyright (C) 2012, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: HYDROGEN GENERATION PROPERTIES; COBALT-PHOSPHORUS CATALYSTS; HYDROLYSIS; CO